Defining the Anti-Cancer Activity of Tricarbonyl Rhenium Complexes: Induction of G2/M Cell Cycle Arrest and Blockade of Aurora-A Kinase Phosphorylation - Simpson, Peter; Casari, Ilaria; Paternoster, Silvano; Skelton, B.; Falasca, Marco; Massi, Massimiliano (Wiley - V C H Verlag GmbH & Co. KGaA, 2017)
Rhenium and ruthenium complexes containing N-heterocylic carbene (NHC) ligands and conjugated to indomethacin were prepared. The anticancer properties were probed against pancreatic cell lines, revealing a remarkable activity of the rhenium fragment as anticancer agent. The ruthenium complexes were found to be inactive against the same pancreatic cancer cell lines, either alone or in conjugation with indomethacin. An in-depth biological study revealed the origin of the anticancer properties of the rhenium tricarbonyl fragment, of which a complete elucidation had yet to be achieved. It was found that the rhenium complexes induce cell cycle arrest at the G2/M phase by inhibiting the phosphorylation of Aurora-A kinase. A preliminary study on the structure-activity relationship on a large family of these complexes revealed that the anticancer properties are mainly associated with the lability of the ancillary ligand, with inert complexes showing limited to no anticancer properties.